Etika Periklanan Sebagai Upaya Menyeimbangkan Strategi Pemasaran & Tanggung Jawab Sosial - Siska Aulia; Zahra Anastasia; Laily Rhomadona; Cinta Mayra Zetha; Daniel Handoko (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Advertising not only serves as a promotional tool, but also reflects corporate social responsibility. This research aims to analyze the relationship between marketing strategy and the application of ethics in advertising, using a descriptive qualitative approach. Tokopedia's “Selalu Ada Selalu Bisa” campaign was used as the main case study to examine ethical communication practices in advertising. The results show that advertisements that emphasize honesty, transparency, and social empathy are able to build consumer trust, strengthen brand image, and increase loyalty. Conversely, misleading advertisements or exploitation of vulnerable groups can damage reputation and public trust. In the fast-paced digital era, a mix of formal regulation and self-regulation is important to maintain the ethics of marketing communications. This study concludes that ethics is not an obstacle to creativity, but rather a strategic foundation that strengthens business sustainability and long-term relationships with society.